H2 antagonists in the treatment of reflux oesophagitis: can physiological studies predict the response?. Issue 8 (August 1987) - Robertson, D A; Aldersley, M A; Shepherd, H; Lloyd, R S; Smith, C L
Abstract : Ambulatory oesophageal pH, oesophageal manometry and fasting serum gastrin concentrations were carried out on 28 patients with reflux oesophagitis, before and during treatment with ranitidine 300 mg bd. Fourteen patients healed endoscopically at six weeks (group A) and 14 had residual oesophagitis (group B). Group A were characterised by a lower serum gastrin concentration before treatment (4.52 pmol/l; 2.4-10: mean and range) than group B (11.1 pmol/l; 3.5-21: p less than 0.05) and showed a marked reduction in acid reflux on treatment to near normal values. Mean per cent time below pH4 fell from 14.9 to 4.2 in group A (p less than 0.05) but was not affected in group B (14.2-15.6, not significant). Abnormal oesophageal motility was found in 13 patients from each group. This did not inhibit the response to ranitidine, and was not improved by healing of oesophagitis.